Cardiovascular autonomic nervous function in 7–12 years old children conceived naturally or by ART with frozen and fresh embryo transfer. (3rd October 2022) - Mizrak, I; Lund, M A V; Landgrebe, A V; Asserhoej, L L; Gorm, G; Clausen, T D; Main, K M; Vejlstrup, N G; Jensen, R B; Pinborg, A; Madsen, P L
Abstract: Background: Cardiovascular autonomic nervous functions (CANF) exert important homeostatic mechanisms to prevent major arterial blood pressure fluctuations by adjusting heart rate (HR), cardiac contractility, and peripheral vascular tone. Children conceived by assisted reproductive technologies (ART) are at risk of increased carotid intima-media thickness, insulin resistance, arterial stiffness, and hypertension. CANF is impaired in children with obesity and diabetes mellitus, and conductance artery stiffness is documented to influence CANF. CANF may therefore be hypothetized to be impaired in children conceived by ART. Purpose: This is the first study to investigate whether children conceived by ART have impaired CANF as compared to naturally conceived children. Method: CANF was studied in 105 singletons aged 7–12 years conceived naturally (NC, N=33) or by ART (frozen embryo transfer (FET, N=34) and fresh embryo transfer (Fresh ET, N=38)). CANF was evaluated with continuous non-invasive hemodynamic measurements (Finapres®) by the HR and blood pressure changes seen relative to rest during active standing, deep breathing and Valsalva, respectively. Results: The descriptive data showed no difference in CANF measurements between our study groups (Table 1). In the multivariate analysis, only the Valsalva HR-ratio to rest was significantly higher in children conceived by FET as compared to NC children after adjustments for age, sex, BMI and maternal age at delivery (Figure 1). For all meaures, the effect size (Hedges d) ranged from 0.02 to 0.48. Conclusion: In this study only the Valsalva HR-response between FET and NC groups were statistically significant after adjustment for confounders, and in general effect sizes were small. Our study suggests that children conceived by ART do not have a significantly impaired cardiovascular autonomic nervous function as compared to naturally conceived children. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Novo Nordisk Foundation